Organometallics in synthesis : third manual - Schlosser, M. (Manfred); Schlosser, M. (Manfred) (Hoboken, New Jersey : Wiley, 2013)
"Organometallics in Synthesis: A Manual, Third Edition is an essential resource for all synthetic organic chemists. The content and topics covered are completely new from the Second Edition, with an eye towards providing the most useful and practical reference on organometallics for practicing researchers. Background information about the organometallic class, the various methods to prepare organometallic compounds, and their use in synthetic reactions are coupled with mechanistic considerations and future research opportunities for each organometallic class. Interspersed throughout are hands-on, practical examples of the preparation of organometallics and their applications in organic synthesis - these are easy to follow with a recipe-like format, all thoroughly referenced to the primary literature"--
"Offers an essential resource for all synthetic organic chemists, featuring chapters for preparing and utilizing the most important and relevant organometallic compounds in organic synthesis"--
Organoalkali chemistry / Manfred Schlosser -- Organomagnesium and organozinc chemistry / Paul Knochel -- Organosilicon and organotin chemistry / Tamejiro Hiyama -- Organoiron chemistry / Hans-Joachim Knölker -- Organopalladium chemistry / Stefan Brase.
Machine generated contents note: List of Contributors VII Preface IX Organoalkali Chemistry 1 219 Manfred Schlosser Organomagnesium and Organozink Chemistry 221 Paul Knochel Organosilicium and Organotin Chemistry Tamejiro Hiyama Organoiron Chemistry Hans-Joachim Knolker Organopalladium Chemistry Stefan Brase.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Organic compounds -- Synthesis; Organometallic compounds; SCIENCE -- Chemistry -- Organic; Organic compounds -- Synthesis; Organometallic compounds; Electronic books; Electronic books